Atypical Lymphoid Proliferations and Clonality in Helicobacter-associated Inflammatory Infiltrates in Children. (October 2019) - Ju, Jennifer Y.; Stelow, Edward B.; Mahadevan, Mani S.; Fan, Jinbo; Aguilera, Nadine S.
Abstract : Helicobacter infection is considered the major predisposing factor for gastric mucosa-associated lymphoid tissue (MALT) lymphoma with initial infection likely occurring in childhood. Primary gastric MALT lymphoma most commonly occurs in patients older than 50 years which is attributed to the lengthy chronic infection time required before the development of MALT lymphoma. Our study analyzes the histologic features and presence of immunoglobulin heavy chain ( IGH ) clonality in Helicobacter -associated chronic gastritis (62 cases) and Helicobacter -negative chronic gastritis (17 cases) biopsies within the pediatric population, diagnosed between 1996 and 2018. Helicobacter -associated gastritis was more likely to show active inflammation ( P =0.01), with no significant difference in number of germinal centers or the strength, linear property, or depth of the inflammatory infiltrate. In total, 47% (29/62) of the Helicobacter -associated cases had at least 1 lymphoepithelial lesion, equivocal or definitive (a modified Wotherspoon score of 3 to 5), compared with 24% (4/17) of the Helicobacter -negative cases ( P =0.5). All cases with lymphoepithelial lesions were assessed for IGH clonality, showing the presence of monoclonality in 27% (8/30) of evaluable cases. None of our patients were diagnosed with gastric lymphoma within available follow-up data. Although 4% of our cases could be considered MALT lymphoma in an adult patient based on prominent lymphoepithelial lesions and IGH monoclonality, caution is advised when diagnosing lymphoma in the pediatric population given the good prognosis of Helicobacter -associated gastritis in this age group. It is unclear if these monoclonal lymphoid proliferations require close follow-up.